“Buyurdum ki….” – The Whole World of Ottomanica and Beyond
1 online resource (800 pages)
Keywords: This book is dedicated to Claudia Römer and brings together 33 contributions spanning a period from the 15th to the 20th century and covering the wide range of topics with which the honouree is engaged. The volume is divided into six parts that present current research on language, literature, and style as well as newer approaches and perspectives in dealing with sources and terminologies. Aspects such as conquest, administration, and financing of provinces are found as well as problems of endowments and the circulation of goods in the Arab provinces of the Ottoman Empire. Another main topic is dedicated to minorities and their role and situation in various provinces and cities of the Ottoman Empire, as represented by various sources. But also topics like conversion, morality and control are illuminated. Finally, the volume provides an insight into the late Ottoman and early republican period, in which some previously unpublished sources (such as travel letters, memoirs) are presented and (re)discussed. The book is not only aimed at scholars and students of the Ottoman Empire; the thematic range is also of interest to linguists, historians, and cultural historians.